GAYA KEPEMIMPINAN TECHNOPRENEUR KEPALA SEKOLAH DAN DAMPAKNYA TERHADAP MUTU PENDIDIKAN SERTA PENGEMBANGAN KEWIRAUSAHAAN DI SMP UNGGUL DARUL UCHWAH: Kepemimpinan Technopreneur; Mutu Pendidikan; Kewirausahaan; Pendidikan Inovatif. - Rahmawati, Ima; As shidqi, Reva Luthfiah; Lestari, Hana (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2025)
This study aims to explore the leadership style of principals who are oriented towards technopreneurship on the quality of education and the development of entrepreneurial skills at SMP Unggul Darul Uchwah. Using a qualitative approach with a case study design, data is collected through in-depth interviews, observations, and document analysis. The results of the study show that school principals have succeeded in creating an innovative and collaborative learning environment, increasing student participation in entrepreneurial activities, and encouraging creativity and practical skills. In addition, the application of technology in the learning process is also a key factor in improving the quality of education. However, challenges related to facilities and resources still need to be addressed to ensure the sustainability of the program. This study recommends the need for closer collaboration with higher education institutions to support the development of relevant curricula and strengthen connectivity between theory and practice in entrepreneurship education. It is hoped that these findings can be a reference for the development of education policies that are more responsive and adaptive to the needs of students in facing global challenges.